PENGARUH KOMPENSASI, KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Wulan Nuriana; Tjiptogoro Dinarjo Soehari (Akademika : Jurnal Teknologi Pendidikan, 2019)
This study aims to examine and analyze the effect of Compensation, Leadership and Motivation to the employee performance in Water Treatment Plant (WTP) PT. Multi Artha Pratama. This study is a quantitative research method. The sampling technique uses a saturated sampling of 50 employees as respondents. The data analitycal is multiple linear regression. The results showed that Compensation and Leadership have positive affect the performance of the employee while, motivation have significant and positive effect on the variable performance of the employee with a strong degree of correlation. Compensation, Leadership and Motivation jointly and significant positive effection the variable performance of the employee performance. The researchers suggest is that the motivation needs to be higher for the performance of employees in WTP PT. Multi Artha Pratama over rise.